2012
DOI: 10.1590/s0102-86502012000700013
|View full text |Cite
|
Sign up to set email alerts
|

New suture techniques for best esthetic skin healing

Abstract: PURPOSE:To report two new suture techniques for best esthetic skin healing. METHODS: Using the pig skin slices routinely employed for surgical technique training two new types of skin sutures were performed.One defined as inverted or hidden X point suture and other as totally hidden intradermal running suture. The first were performed using 4-0 polypropilene stitch and the intradermal with 4-0 poliglicolic stitch. RESULTS:It was confirmed good skin layers union and contention with best esthetic result than obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…The hidden X suture, which was first presented in a plastic surgery study, is a modification of the conventional X suture (Figure 3) [14]. In plastic surgery, it has also been reported that the hidden X suture has certain advantages over the conventional X suture.…”
Section: Introductionmentioning
confidence: 99%
“…The hidden X suture, which was first presented in a plastic surgery study, is a modification of the conventional X suture (Figure 3) [14]. In plastic surgery, it has also been reported that the hidden X suture has certain advantages over the conventional X suture.…”
Section: Introductionmentioning
confidence: 99%
“…Na sutura do tipo simples interrompida, o espaço entre os pontos pode afetar o início do processo de cicatrização, além disso, o espaçamento entre os pontos diminui o trauma do tecido e economiza o tempo cirúrgico 25 . A sutura intradérmica comum exibe somente as bordas do primeiro e último nós da sutura, promovendo boa síntese do tecido e bom resultado estético, mas as pontas expostas da sutura podem promover acesso bacteriano e infecção subcutânea 26 . Nos casos apresentados nesse artigo, todos obtiveram boas cicatrizações, no entanto, no caso em que foi usada a sutura interrompida simples, ocorreu melhor cicatrização.…”
Section: Discussionunclassified
“…The inverse figure 8 suture technique has been utilized successfully by periodontists and surgeons for years. 1 , 2 Maybe it’s time we teach the inverse of a surgical technique mainstay to our trainees too.…”
Section: Solutionmentioning
confidence: 99%